Combined clinical and research training in medical physics in a multi‐institutional setting: 13‐year experience of Harvard Medical Physics Residency Program. Issue 1 (8th November 2022) - Lyatskaya, Yulia; Winey, Brian; Kiger, W. S.; Hurwitz, Martina; Zygmanski, Piotr; Makrigiorgos, G. Mike; Bortfeld, Thomas R.; Doppke, Karen P.; Lu, Xing‐Qi; Chin, Lee M.; Biggs, Peter; Gierga, David P.
Abstract: Purpose: This manuscript describes the structure, management and outcomes of a multi‐institutional clinical and research medical physics residency program (Harvard Medical Physics Residency Program, or HMPRP) to provide potentially useful information to the centers considering a multi‐institutional approach for their training programs. Methods: Data from the program documents and public records was used to describe HMPRP and obtain statistics about participating faculty, enrolled residents, and graduates. Challenges associated with forming and managing a multi‐institutional program and developed solutions for effective coordination between several clinical centers are described. Results: HMPRP was formed in 2009 and was accredited by the Commission on Accreditation of Medical Physics Education Programs (CAMPEP) in 2011. It is a 3‐year therapy program, with a dedicated year of research and the 2 years of clinical training at three academic hospitals. A CAMPEP‐accredited Certificate Program is embedded in HMPRP to allow enrolled residents to complete a formal didactic training in medical physics if necessary. The clinical training covers the material required by CAMPEP. In addition, training in protons, CyberKnife, MR‐linac, and at network locations is included. The clinical training and academic record of the residents is outstanding. All graduates have found employment within clinical medical physics, mostly at large academic centers and graduates had a 100% pass rate at the oral American Board of Radiology exams. On average, three manuscripts per resident are published during residency, and multiple abstracts are presented at conferences. Conclusions: A multi‐institutional medical physics residency program can be successfully formed and managed. With a collaborative administrative structure, the program creates an environment for high‐quality clinical training of the residents and high productivity in research. The main advantage of such program is access to a wide variety of resources. The main challenge is creating a structure for efficient management of multiple resources at different locations. This report may provide valuable information to centers considering starting a multi‐institutional residency program.